Pengembangan E-Modul Perawatan Tangan Menggunakan Platform Canva: Penerapan Model ADDIE dan Evaluasi Efektivitas Pembelajaran - Faradila Lativa Ahmad (Mathematics Education Study Program, 2025)
This study aims to develop an E-Module of Essential Oils for Hand Care using the Canva platform at SMK 27 Jakarta. The method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which includes analysis, design, development, implementation, and evaluation. This study targets students of the beauty program. The resulting E-Module contains interactive learning media to increase reading interest and understanding of the material. The validation results by material experts showed a feasibility percentage of 93.15%, while from media experts it reached 94.73%, both of which were categorized as very feasible. The trial on students showed a pre-test value of 92.78% and increased by 0.96% to 93.74% after the post-test. This shows that the developed E-Module is effective in improving students' hand care skills. This research is expected to provide a positive contribution to the learning process at SMK 27 Jakarta by utilizing digital technology for education.